Comparison of Human and Soil Candida tropicalis Isolates with Reduced Susceptibility to Fluconazole - Yang, Yun-Liang; Lin, Chih-Chao; Chang, Te-Pin; Lauderdale, Tsai-Ling; Chen, Hui-Ting; Lee, Ching-Fu; Hsieh, Chih-Wen; Chen, Pei-Chen; Lo, Hsiu-Jung (PLOS ONE, 2012)
Infections caused by treatment-resistant non-albicans Candida species, such as C. tropicalis, has increased, which is an emerging challenge in the management of fungal infections. Genetically related diploid sequence type (DST) strains of C. tropicalis exhibiting reduced susceptibility to fluconazole circulated widely in Taiwan. To identify the potential source of these wildly distributed DST strains, we investigated the possibility of the presence in soil of such C. tropicalis strains by pulsed field gel electrophoresis (PFGE) and DST typing methods. A total of 56 C. tropicalis isolates were recovered from 26 out of 477 soil samples. Among the 18 isolates with reduced susceptibility to fluconazole, 9 belonged to DST149 and 3 belonged to DST140. Both DSTs have been recovered from our previous studies on clinical isolates from the Taiwan Surveillance of Antimicrobial Resistance of Yeasts (TSARY) program. Furthermore, these isolates were more resistant to agricultural azoles. We have found genetically related C. tropicalis exhibiting reduced susceptibility to fluconazole from the human hosts and environmental samples. Therefore, to prevent patients from acquiring C. tropicalis with reduced susceptibility to azoles, prudent use of azoles in both clinical and agricultural settings is advocated.